Self-supporting ceramic separator for electrochemical device and electrochemical device comprising same
By using a self -supported ceramic diaphragm that uses non -porous polymer substrates in the electrochemical device, combined with the combination of first and second inorganic particles, solving the short circuit problem caused by polyolefins resin at high temperature, realized Higher heat resistance and battery life.
Patent Information
- Application Number
- CN202480003106.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-19
- Filing Date
- 2024-04-15
- Publication Date
- 2025-01-24
AI Technical Summary
In existing electrochemical devices, polyolefin resin shrinks at high temperatures and causes electrode contact, causing power short circuits and thermal runaway, affecting the safety and life of the battery.
A self-supporting ceramic separator without a porous polymer substrate is used, and by combining first inorganic particles and second inorganic particles in the separator, a dense stacked structure with a sheet shape and an adsorption structure with a high specific surface area are formed to improve Diaphragm heat resistance and durability.
Effectively inhibits thermal shrinkage at high temperatures, prevents electrode contact, improves battery stability and life characteristics, and improves battery safety.
Smart Images

Figure CN119366048A_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2023-0051554 filed in the Korean Intellectual Property Office on April 19, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present disclosure relates to a self-supporting ceramic diaphragm for an electrochemical device and an electrochemical device comprising the same, and in particular to a self-supporting ceramic diaphragm for an electrochemical device having improved heat resistance and exhibiting high battery life characteristics by comprising first inorganic particles and second inorganic particles, and an electrochemical device comprising the same. Background Art
[0003] Among the components of an electrochemical device, a separator includes a polymer substrate having a porous structure disposed between a positive electrode and a negative electrode, and serves to separate the positive electrode and the negative electrode to prevent electrical short circuits between the two electrodes and to transmit electrolytes and ions. The separator itself does not participate in the electrochemical reaction, but the physical properties of the separator, such as wettability to the electrolyte, degree of porosity, thermal shrinkage, etc., affect the performance and safety of the electrochemical device.
[0004] Therefore, in order to improve the physical properties of the separator, various methods of adding a coating to a porous polymer substrate and adding various materials to the coating to change the physical properties of the coating have been tried. For example, in order to improve the mechanical strength of the separator, an inorganic substance may be added to the coating, or an inorganic substance or a hydrate for improving the flame retardancy and heat resistance of the polymer substrate may be added to the coating.
[0005] The separator may be bonded to the electrode through a lamination process, and in order to ensure bonding strength between the electrode and the separator, a polymer binder may be added to the coating composition of the separator.
[0006] On the other hand, polyolefin-based resins widely used as porous polymer substrates for electrochemical devices have the following problems: when the polyolefin-based resins are exposed to high temperatures, the positive electrode and the negative electrode come into contact with each other due to the shrinkage of the polyolefin-based resins, so that an electrical short circuit occurs between the two electrodes, and the electrolyte and the active material undergo a decomposition reaction due to heat generation, thereby causing thermal runaway.
[0007] Therefore, it is necessary to develop a self-supporting ceramic separator that can improve heat resistance and durability by appropriately combining inorganic particles without containing polyolefin resins (i.e., porous polymer substrates), and can improve battery safety and battery life characteristics by preventing electrical short circuits between electrodes. Summary of the invention
[0008] Technical issues
[0009] The technical purpose to be achieved by the present disclosure is to provide a self-supporting ceramic diaphragm for an electrochemical device having a structure comprising first inorganic particles and second inorganic particles and not containing a porous polymer substrate, and an electrochemical device comprising the same, wherein the first inorganic particles form a dense stacking structure having a flaky shape, thereby preventing transition metals dissolved from the positive electrode from transferring to the surface facing the negative electrode, and the second inorganic particles have a high specific surface area and can adsorb gases and transition metals, so that the diaphragm can improve heat resistance and durability, and can improve battery stability and battery life characteristics.
[0010] However, the objects to be achieved by the present disclosure are not limited to the aforementioned objects, and other objects not described above may be clearly understood by those skilled in the art from the following description.
[0011] Technical Solution
[0012] One embodiment of the present disclosure provides a self-supporting ceramic diaphragm for an electrochemical device, comprising first inorganic particles, second inorganic particles, and a polymer binder, wherein the first inorganic particles have a flaky shape and an aspect ratio of the first inorganic particles is greater than or equal to 10 and less than or equal to 300.
[0013] According to one embodiment of the present disclosure, one surface of the first inorganic particle and one surface of the separator may be arranged to face each other.
[0014] According to one embodiment of the present disclosure, it may also include: a first layer, wherein the weight of the first inorganic particles contained therein is greater than the weight of the second inorganic particles contained therein; and a second layer, arranged on a surface of the first layer, wherein the weight of the second inorganic particles contained therein is greater than the weight of the first inorganic particles contained therein.
[0015] According to one embodiment of the present disclosure, a surface of the first layer opposite to the one surface may be disposed to face the negative electrode.
[0016] According to one embodiment of the present disclosure, the first inorganic particles may include one selected from the group consisting of boron nitride, boehmite, kaolin, and a combination thereof.
[0017] According to one embodiment of the present disclosure, the second inorganic particles may be zeolite-based inorganic particles. The second inorganic particles may include pores having a diameter of 0.5 nm or more and 0.9 nm or less. The pores of the second inorganic particles may be replaced by metal ions.
[0018] According to one embodiment of the present disclosure, the average particle size D50 of the second inorganic particles may be less than 1 μm.
[0019] According to one embodiment of the present disclosure, the thickness of the second layer may be 1 μm or more and 3 μm or less.
[0020] According to one embodiment of the present disclosure, the content of the first inorganic particles may be 5 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the separator.
[0021] According to one embodiment of the present disclosure, the polymer binder may be an acrylic binder, a polyvinylidene binder, or a combination thereof.
[0022] According to one embodiment of the present disclosure, the thickness of the separator may be 7 μm or more and 15 μm or less.
[0023] According to one embodiment of the present disclosure, the air permeability of the separator may be 170 sec / 100 cc or less.
[0024] According to one embodiment of the present disclosure, the electrical resistance of the separator may be 0.6Ω or more and 1.2Ω or less.
[0025] One embodiment of the present disclosure provides an electrochemical device including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode.
[0026] Beneficial Effects
[0027] A self-supporting ceramic separator for an electrochemical device according to one embodiment of the present disclosure can suppress thermal shrinkage at high temperatures.
[0028] The self-supporting ceramic separator for an electrochemical device according to one embodiment of the present disclosure can improve the stability and battery life characteristics of a battery by preventing a transition metal dissolved from a positive electrode from transferring to a surface facing a negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of a self-supporting ceramic separator for an electrochemical device according to one embodiment of the present disclosure.
[0030] Figure 2 is a schematic diagram of an electrochemical device according to one embodiment of the present disclosure. DETAILED DESCRIPTION
[0031] In the present specification, when it is mentioned that a certain part “comprises” a certain constituent element, it does not mean that other constituent elements are excluded, but other constituent elements may be further included unless explicitly stated otherwise.
[0032] In the present specification, "A and / or B" means "A and B, or A or B".
[0033] In the present specification, when it is mentioned that a constituent element is disposed “on” another constituent element, unless explicitly stated otherwise, it means that other constituent elements may be disposed between the two constituent elements, and does not exclude the presence of other constituent elements.
[0034] In this specification, the property of “having pores” means that since an object includes a plurality of pores, a structure in which the pores are connected to each other enables gaseous and / or liquid fluids to flow from one side of the object to the other side.
[0035] In this specification, the separator has a porous property including a plurality of pores, and functions as an ion conductive barrier in an electrochemical device, which transmits ions while blocking electrical contact between a negative electrode and a positive electrode.
[0036] Hereinafter, the present disclosure is described in more detail.
[0037] One embodiment of the present disclosure provides a self-supporting ceramic separator for an electrochemical device, comprising first inorganic particles, second inorganic particles, and a polymer binder, wherein the first inorganic particles have a flaky shape and an aspect ratio of the first inorganic particles is greater than or equal to 10 and less than or equal to 300.
[0038] The self-supporting ceramic separator for an electrochemical device according to one embodiment of the present disclosure can suppress thermal shrinkage at high temperatures. In addition, the self-supporting ceramic separator for an electrochemical device according to one embodiment of the present disclosure can improve the stability of the battery and the life characteristics of the battery by preventing the transition metal dissolved from the positive electrode from transferring to the surface facing the negative electrode.
[0039] Figure 1 Schematic diagram of a self-supporting ceramic diaphragm for an electrochemical device according to one embodiment of the present disclosure. Figure 1 , a self-supporting ceramic diaphragm for an electrochemical device as one embodiment of the present disclosure is described in detail. Figure 2 Schematic diagram of an electrochemical device according to one embodiment of the present disclosure. Figure 2 , an electrochemical device as one embodiment of the present disclosure is described in detail.
[0040] According to one embodiment of the present disclosure, the self-supporting ceramic separator 100 for an electrochemical device does not contain a porous polymer substrate. Since the self-supporting ceramic separator for an electrochemical device does not contain a porous polymer substrate, the heat resistance of the separator can be improved, and the occurrence of electrical short circuits in electrodes caused by shrinkage of the separator at high temperatures can be prevented.
[0041] According to one embodiment of the present disclosure, the separator 100 includes first inorganic particles, second inorganic particles, and a polymer binder. Since the separator includes first inorganic particles, second inorganic particles, and a polymer binder as described above, the heat resistance of the separator can be improved, and the occurrence of electrical short circuits in the electrodes caused by shrinkage of the separator at high temperatures can be prevented. In addition, holes can be formed inside the separator.
[0042] According to one embodiment of the present disclosure, the separator 100 may include a plurality of pores. Specifically, the separator may be a porous separator including a plurality of pores therein. Since the separator includes a plurality of pores as described above, physical contact between the negative electrode and the positive electrode can be prevented, and since lithium ions pass through the separator, current can flow through the separator.
[0043] According to one embodiment of the present disclosure, the separator 100 may be formed in a manner in which the polymer binder bonds the inorganic particles and the inorganic particles accumulate on the side. The pores in the separator may be caused by interstitial volumes (i.e., gaps between the inorganic particles). Specifically, as described later, the structure and size of the pores may be different depending on the shape and combination of the first inorganic particles and the second inorganic particles. In addition, due to the difference in the structure and size of the pores, it is possible to prevent the transition metal dissolved from the positive electrode from being transferred to the surface facing the negative electrode.
[0044] According to one embodiment of the present disclosure, the inorganic particles may include the first inorganic particles and the second inorganic particles. Non-limiting examples of the inorganic particles may include BaTiO3, Pb(Zr,Ti)O3(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT、0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3)O3-PbTiO3 (PMN-PT), hafnium dioxide (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc tin hydroxide (ZnSn(OH)6), zinc tin oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), antimony pentoxide (Sb2O5), zeolite A, zeolite X, zeolite Y, etc., and the inorganic particles may include one or more of them. On the other hand, in addition to the examples, the inorganic particles may include boron nitride (BN), boehmite and kaolin. One or more inorganic particles with a flaky shape.
[0045] According to one embodiment of the present disclosure, the first inorganic particles have a flake shape. Since the first inorganic particles have a flake shape as described above, a dense stacking structure can be formed, thereby improving the durability of the separator.
[0046] According to one embodiment of the present disclosure, the aspect ratio of the first inorganic particle is 10 to 300. As described above, the first inorganic particle is an inorganic particle having a flake shape, and the aspect ratio thereof may be 10 to 300. More specifically, the first inorganic particle is an inorganic particle having a flake shape, and the aspect ratio thereof may be 20 to 290, 30 to 280, 40 to 270, 50 to 260, 60 to 250, 70 to 240, 80 to 230, 90 to 220, 100 to 210, 110 to 200, 120 to 190, 130 to 180, 140 to 170, or 150 to 160. In the present specification, the aspect ratio may be defined as [length in the long axis direction] / [width in the direction orthogonal to the long axis direction] of the inorganic particles having a flaky shape. By adjusting the aspect ratio of the first inorganic particles within the aforementioned range, the coating thickness can be reduced, and since a dense stacking structure can be formed, the durability of the separator can be improved.
[0047] According to one embodiment of the present disclosure, one surface of the first inorganic particle and one surface of the separator may be arranged to face each other. As described above, the first inorganic particle is an inorganic particle having a flaky shape and having a shape that is long in the direction of its major axis. Therefore, since the major axis direction is arranged to face one surface of the separator to form a dense stacking structure, the durability of the separator can be improved. In addition, since a complex pore structure is formed, it is possible to suppress the transition metal dissolved from the positive electrode from being transferred to the surface facing the negative electrode.
[0048] According to one embodiment of the present disclosure, a first layer 110 may be included, wherein the weight of the first inorganic particles included is greater than the weight of the second inorganic particles included; and a second layer 130, which is disposed on a surface of the first layer, wherein the weight of the second inorganic particles included is greater than the weight of the first inorganic particles included. Specifically, the first inorganic particles and the second inorganic particles may be mixed in the first layer and the second layer, but the first layer (the first inorganic particles having a heavier weight) and the second layer (the second inorganic particles having a heavier weight) may be stacked separately. Since the first layer and the second layer are stacked separately as described above, the second layer can adsorb gas and transition metals, and the first layer can suppress the occurrence of battery short circuits by preventing the transition metal adsorbed by the second layer from being transferred to the surface facing the negative electrode.
[0049] According to one embodiment of the present disclosure, a surface of the first layer opposite to the one surface may be disposed to face the negative electrode 300 . Figure 2 Schematic diagram of an electrochemical device according to one embodiment of the present disclosure. Figure 2 , the first layer including an excess of the first inorganic particles or only the first inorganic particles can be formed in contact with the negative electrode. As described above, the second layer is provided on one surface of the first layer, and the surface of the first layer opposite to the one surface is provided to face the negative electrode. Therefore, the first layer can suppress the occurrence of battery short circuit by preventing the transition metal dissolved from the positive electrode (if the transition metal is not adsorbed by the second layer but passes through the second layer) from being transferred to the surface facing the negative electrode.
[0050] According to one embodiment of the present disclosure, the first inorganic particles may include one selected from the group consisting of boron nitride, boehmite, kaolin and a combination thereof. As described above, the first inorganic particles may be inorganic particles having a flaky shape. Specifically, since the first inorganic particles include boron nitride (BN) having a hexagonal crystal structure, boehmite (AlOOH) having a hexagonal crystal structure, and kaolin (Al2O3·2SiO2·2H2O) and other clay powders having a flaky shape, the first layer of the first inorganic particles having a heavier weight can be configured to face a surface of the diaphragm to form a dense stacking structure. In addition, since a complex pore structure is formed between the inorganic particles having a flaky shape through a dense stacking structure, it is possible to inhibit the transition metal dissolved from the positive electrode from being transferred through the diaphragm to the surface facing the negative electrode.
[0051] According to one embodiment of the present disclosure, the second inorganic particles may be zeolite-based inorganic particles. Specifically, the zeolite-based inorganic particles may include one selected from the group consisting of zeolite A, zeolite X, zeolite Y, zeolite L, ZSM-5, β-zeolite, ZSM-8, ZSM-11, and combinations thereof. The zeolite-based inorganic particles may have a high specific surface area. Preferably, the zeolite-based inorganic particles may be zeolite Y. Since the zeolite-based inorganic particles are used as the second inorganic particles as described above, the adsorption capacity for gases and transition metals can be improved.
[0052] According to one embodiment of the present disclosure, the second inorganic particle may include a hole having a diameter of 0.5 nm or more and 0.9 nm or less. Specifically, the second inorganic particle includes a space inside the particle, and the diameter of the internal space may be 0.5 nm or more and 0.9 nm or less. In addition, the diameter of the hole may refer to the longest length of the lengths of the two points where a straight line passing through the inside of the hole intersects with the surface of the hole. More specifically, the hole of the second inorganic particle may have a diameter of 0.55 nm or more and 0.85 nm or less, 0.6 nm or more and 0.8 nm or less, or 0.65 nm or more and 0.75 nm or less. By adjusting the diameter of the hole within the aforementioned range, the ability to adsorb gases (such as carbon monoxide (CO) or carbon dioxide (CO2)) generated by lithium-ion batteries can be improved.
[0053] According to one embodiment of the present disclosure, the pores of the second inorganic particles may be replaced by metal ions. Specifically, the metal ions may be metal ions having the same electronegativity as lithium ions or having lower electronegativity than lithium ions. More specifically, the metal ions may be alkali metal ions. Preferably, the metal ions may be one selected from the group consisting of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs) and combinations thereof. By replacing the metal ions selected from the group into the pores of the second inorganic particles, the conductivity of the battery can be maintained because the excess manganese ions contained in the positive electrode active material are adsorbed and the replaced lithium ions are dissolved into the electrolyte. Moreover, the lithium dendrites generated by the accumulation of manganese (i.e., the transition metal moving from the positive electrode to the negative electrode) on the negative electrode can be reduced.
[0054] According to one embodiment of the present disclosure, the average particle size D50 of the second inorganic particles may be greater than 0.3 μm and less than 1 μm. Specifically, the average particle size D50 of the second inorganic particles may be greater than 0.4 μm and less than 0.9 μm, greater than 0.5 μm and less than 0.8 μm, or greater than 0.6 μm and less than 0.7 μm. By adjusting the average particle size D50 of the second inorganic particles within the aforementioned range, the phase separation rate and phase separation efficiency between the polymer binder and the second inorganic particles can be improved in the coating slurry (i.e., an emulsion obtained by dispersing a polymer binder in water). In addition, when the average particle size is less than 0.3 μm, the dispersibility of the second inorganic particles may be reduced in the slurry prepared for manufacturing the diaphragm. When the average particle size is greater than 1 μm, the thickness of the formed diaphragm may increase.
[0055] In this specification, "D50 particle size" refers to the particle size at the 50% point of the cumulative volume distribution of the number of particles according to the particle size. The particle size can be measured using a laser diffraction method. Specifically, after the measurement target powder is dispersed in a dispersion medium, the powder is introduced into a commercially available laser diffraction particle size measuring device (e.g., S3500 of Microtrac). The distribution of particle size is calculated by measuring the difference between the diffraction patterns according to the particle size when the particles pass through a laser beam. The D50 particle size can be measured by calculating the particle size at the 50% point of the cumulative distribution of the number of particles according to the particle size in the measuring device.
[0056] According to one embodiment of the present disclosure, the inorganic particles that can be used in the separator can be electrochemically stable. That is, the inorganic particles that can be used in one embodiment of the present disclosure can be used within the operating voltage range of the electrochemical device used (e.g., Li / Li + As a benchmark, no oxidation and / or reduction reaction occurs within the range of 0V to 5V).
[0057] According to one embodiment of the present disclosure, the thickness of the second layer may be greater than 1 μm and less than 3 μm. Specifically, the thickness of the second layer may be greater than 1.1 μm and less than 2.9 μm, greater than 1.2 μm and less than 2.8 μm, greater than 1.3 μm and less than 2.7 μm, greater than 1.4 μm and less than 2.6 μm, greater than 1.5 μm and less than 2.5 μm, greater than 1.6 μm and less than 2.4 μm, greater than 1.7 μm and less than 2.3 μm, greater than 1.8 μm and less than 2.2 μm, or greater than 1.9 μm and less than 2.1 μm. As described above, since the average particle size D50 of the second inorganic particles constituting the second layer is less than 1 μm, the thickness of the second layer can be adjusted within the aforementioned range.
[0058] According to one embodiment of the present disclosure, the content of the first inorganic particles may be 5 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the diaphragm. Specifically, the content of the first inorganic particles may be 6 parts by weight or more and 9 parts by weight or less, or 7 parts by weight or more and 8 parts by weight or less relative to 100 parts by weight of the diaphragm. By adjusting the content of the first inorganic particles within the aforementioned range, the heat resistance of the diaphragm can be improved, and the durability of the coating can be improved.
[0059] According to one embodiment of the present disclosure, the content of the second inorganic particles may be 5 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the diaphragm. Specifically, the content of the second inorganic particles may be 6 parts by weight or more and 9 parts by weight or more, or 7 parts by weight or more and 8 parts by weight or less relative to 100 parts by weight of the diaphragm. By adjusting the content of the second inorganic particles within the aforementioned range, the heat resistance of the diaphragm can be improved, and the adsorption rate of gas and transition metal can be improved.
[0060] According to one embodiment of the present disclosure, the content of the polymer binder may be 5 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the separator. Specifically, the content of the polymer binder may be 6 parts by weight or more and 9 parts by weight or less, or 7 parts by weight or more and 8 parts by weight or less relative to 100 parts by weight of the separator. By adjusting the content of the polymer binder within the aforementioned range, the porosity of the separator can be maintained, and even if the coating is wetted by the electrolyte after battery activation, the bonding strength can be maintained.
[0061] According to one embodiment of the present disclosure, the polymer binder may be a particle type or a non-particle type. Specifically, as described later, the polymer binder may maintain a particle shape without being dissolved by a dispersion medium or a solvent. The polymer binder may be dissolved by a dispersion medium or a solvent and may not maintain a particle shape. By selecting the particle type or the non-particle type polymer binder as described above, the mechanical properties and porosity of the coating may be adjusted.
[0062] According to one embodiment of the present disclosure, the average particle size D50 of the particle-type polymer binder may be 1.0 μm or less. Specifically, the average particle size D50 of the particle-type polymer binder may be 0.10 μm or more and 0.90 μm or less, 0.15 μm or more and 0.85 μm or less, 0.20 μm or more and 0.70 μm or less, 0.25 μm or more and 0.65 μm or less, 0.30 μm or more and 0.60 μm or less, 0.35 μm or more and 0.55 μm or less, or 0.40 μm or more and 0.50 μm or less. By adjusting the average particle size D50 of the particle-type polymer binder within the aforementioned range, the phase separation speed and phase separation efficiency between the particle-type polymer binder and the inorganic particles in the inorganic slurry (i.e., the emulsion obtained by dispersing the particle-type polymer binder in water) can be improved.
[0063] According to one embodiment of the present disclosure, the polymer binder may be an acrylic binder, a polyvinylene binder, or a combination thereof.
[0064] According to one embodiment of the present disclosure, the polymer binder may include two or more polymer binders. As described above, since the polymer binder includes two or more polymer binders, the bonding strength of the separator can be improved, the porosity of the separator can be improved, and both the dry bonding strength before the electrolyte is injected and the wet bonding strength after the electrolyte is injected can be improved.
[0065] According to one embodiment of the present disclosure, the polymer binder may include an acrylic binder. By using the acrylic binder, the porosity of the separator can be maintained, and the bonding strength between the electrode and the separator in the lamination process of the battery is improved, thereby improving the ease of battery manufacturing and stably implementing the stacking process.
[0066] According to one embodiment of the present disclosure, the acrylic adhesive may be a polymer including carboxylic acid ester as a repeating unit, and preferably may be (meth)acrylate or acrylic-styrene copolymer.
[0067] According to one embodiment of the present disclosure, specific examples of the (meth)acrylate may include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, ethylene glycol (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, ethylene di(meth)acrylate, and the like, and may be one or more selected from them. Among them, at least one selected from methyl (meth)acrylate, ethyl (meth)acrylate and 2-ethylhexyl (meth)acrylate is preferred, and methyl (meth)acrylate is particularly preferred.
[0068] According to one embodiment of the present disclosure, the acrylic-styrene copolymer may include an acrylic adhesive. The acrylic adhesive may be a polyacrylate series. For example, the adhesive may be one or more selected from the group consisting of styrene-butadiene rubber, nitrile rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber and acrylate polymers, and may particularly be a copolymer comprising acrylate.
[0069] According to one embodiment of the present disclosure, the polymer binder may include a polyvinylidene-based binder. Specifically, according to one embodiment of the present disclosure, the polyvinylidene-based binder may be a copolymer of polyvinylidene fluoride and hexafluoropropylene. As described above, by selecting the polymer binder as a polyvinylidene-based binder, the porosity of the separator can be maintained, and the bonding strength can be maintained even if the coating is wetted by the electrolyte after the battery is activated. In addition, the rigidity of the battery can be improved, and the bending of the separator can be prevented.
[0070] According to one embodiment of the present disclosure, the polyvinylene-based adhesive may be a water-based adhesive. Specifically, by selecting the polyvinylene-based adhesive as a water-based adhesive, pollutants discharged during the membrane manufacturing process can be minimized and the battery manufacturing cost can be reduced.
[0071] According to one embodiment of the present disclosure, the polyvinylene-based binder may be a polyvinylene-based binder having a hexafluoropropylene content of 1 wt % or more and 50 wt % or less. As described above, by selecting a polyvinylene-based binder having a hexafluoropropylene content of 1 wt % or more and 50 wt % or less as the second polymer binder particles, the porosity of the separator can be maintained, and even if the coating is wetted by the electrolyte after battery activation, the bonding strength can be maintained.
[0072] According to one embodiment of the present disclosure, the thickness of the diaphragm may be greater than 7 μm and less than 15 μm, but the present disclosure is not particularly limited thereto. Specifically, the thickness of the diaphragm may be greater than 8 μm and less than 14 μm, greater than 9 μm and less than 13 μm, or greater than 10 μm and less than 12 μm. Those skilled in the art may adjust the thickness within an appropriate range from the perspective of heat resistance or resistance. As described above, the first inorganic particles having a flaky shape constituting the diaphragm are arranged to face one surface of the diaphragm to form a dense stacking structure, and the average particle size D50 of the second inorganic particles is less than 1 μm. Therefore, the thickness of the diaphragm can be adjusted within a suitable range within the aforementioned range.
[0073] According to one embodiment of the present disclosure, a contact thickness gauge may be used to measure the thickness of the second layer and / or the diaphragm. For example, a VL-50S-B manufactured by Mitutoyo may be used as the contact thickness gauge.
[0074] According to one embodiment of the present disclosure, the air permeability of the diaphragm may be 170 seconds / 100cc or less. Specifically, the air permeability of the diaphragm may be 100 seconds / 100cc or more and 170 seconds / 100cc or less, 110 seconds / 100cc or more and 160 seconds / 100cc or less, 120 seconds / 100cc or more and 150 seconds / 100cc or less, or 130 seconds / 100cc or more and 140 seconds / 100cc or less. As described above, since the inorganic particles have a flaky shape or a small average particle size D50, they may have excellent air permeability.
[0075] According to one embodiment of the present disclosure, the resistance of the diaphragm may be greater than 0.6Ω and less than 1.2Ω. Specifically, the resistance of the diaphragm may be greater than 0.7Ω and less than 1.1Ω, or greater than 0.8Ω and less than 1.0Ω. It is believed that the resistance value of the diaphragm is small because the inorganic particles have a flaky shape or a small average particle size D50 as described above.
[0076] According to one embodiment of the present disclosure, the breakdown voltage of the diaphragm may be 3700 V or more. Specifically, the breakdown voltage of the diaphragm may be 3700 V or more and 5000 V or less, 3800 V or more and 4900 V or less, 3900 V or more and 4800 V or less, 4000 V or more and 4700 V or less, 4100 V or more and 4600 V or less, 4200 V or more and 4500 V or less, or 4300 V or more and 4400 V or less. As can be seen, as described above, since the inorganic particles have a flaky shape or a small average particle size D50, the diaphragm has a high breakdown voltage and excellent voltage resistance characteristics.
[0077] According to one embodiment of the present disclosure, the porosity of the diaphragm may be 30% by volume or more. Specifically, the porosity of the diaphragm may be 30% by volume or more and 70% by volume or less, 32% by volume or more and 68% by volume or less, 34% by volume or more and 66% by volume or less, 36% by volume or more and 64% by volume or less, 38% by volume or more and 62% by volume or less, 40% by volume or more and 60% by volume or less, 42% by volume or more and 58% by volume or less, 44% by volume or more and 56% by volume or less, 46% by volume or more and 54% by volume or less, or 48% by volume or more and 52% by volume or less. By adjusting the porosity of the diaphragm within the aforementioned range, the movement of ions in the diaphragm can be maintained, and the resistance of the diaphragm can be prevented from increasing. Specifically, when the porosity is 70% by volume or less, it is possible to ensure that the mechanical properties that can withstand the pressing process for bonding to the electrode can be ensured. In addition, since the surface opening rate will not become too high, it is suitable for ensuring the bonding strength. On the other hand, when the porosity is 30% by volume or more, it is advantageous in terms of ion permeability.
[0078] In this specification, "porosity" refers to the ratio of the volume occupied by pores to the total volume. Volume % is used as the unit of porosity. Porosity can be used interchangeably with terms such as void fraction or porosity.
[0079] In this specification, the porosity corresponds to a value obtained by subtracting a volume calculated from the weight and density of each component of the separator from a volume calculated from the thickness, width, and height of the separator.
[0080] In one embodiment of the present disclosure, the porosity and pore size of the separator may be measured using a scanning electron microscope (SEM) image, a mercury porosimeter, a capillary flow porosimeter, or a porosity analyzer (Belsorp-II mini of Bell Japan Inc) by a nitrogen adsorption distribution method using a BET six-point method. In this case, the use of a capillary flow porosimeter may be advantageous.
[0081] According to one embodiment of the present disclosure, the formation method of the diaphragm is, for example, as follows. First, a polymer solution or polymer emulsion is manufactured, wherein the polymer binder has been dissolved in a suitable solvent or dispersed in a dispersion medium. Preferably, a solvent or dispersion medium having a similar solubility index and a low boiling point to the polymer binder to be used. This is for uniform mixing and subsequent easy removal of the solvent or the dispersion medium. Non-limiting examples of the solvent or the dispersion medium that can be used include acetone, tetrahydrofuran, dichloromethane, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), cyclohexane, water or a mixture thereof.
[0082] Next, the first inorganic slurry is prepared by adding the first inorganic particles to the manufactured first polymer solution or the first polymer emulsion and dispersing. According to one embodiment of the present disclosure, the content ratio of the first inorganic particles to the polymer binder is as described above, and can be appropriately adjusted considering the thickness, pore size and porosity of the separator according to the present disclosure that is finally manufactured.
[0083] Next, the prepared first inorganic slurry is applied to at least one side of the prepared PET release film and dried. The method of applying the first inorganic slurry to the surface of the PET release film is not specifically limited to any one method, and a common method known in the industry can be used. For example, various methods such as dip coating, die coating, roller coating, comma coating, or a combination thereof can be used.
[0084] Next, the second inorganic slurry is prepared by adding the second inorganic particles to the second polymer solution or the second polymer emulsion manufactured using the same method and dispersing them. According to one embodiment of the present disclosure, the content ratio of the second inorganic particles to the polymer binder is as described above, and can be appropriately adjusted considering the thickness, pore size and porosity of the separator according to the present disclosure that is finally manufactured.
[0085] Next, the prepared second inorganic slurry is applied to the applied first layer containing the first inorganic particles and dried. The method of applying the second inorganic slurry to the surface of the first layer is not specifically limited to any one method, and a common method known in the industry can be used. For example, various methods such as dip coating, die coating, roller coating, comma coating, or a combination thereof can be used.
[0086] In the drying process, temperature and time conditions are appropriately set so that surface defects occurring in the separator can be minimized. For the drying, drying auxiliary equipment such as a drying furnace or hot air may be used within an appropriate range.
[0087] After the drying step, the separator may be manufactured by removing the PET release film.
[0088] According to one embodiment of the present disclosure, the polymer emulsion can be manufactured by dispersing the polymer binder (i.e., the first polymer binder and the second polymer binder) together with a wetting agent in water as a suitable dispersion medium, thereby providing the first inorganic slurry and / or the second inorganic slurry. The wetting agent has 0 to 5 parts, preferably 0 to 3 parts of one or more wetting agents per 100 parts of water, and can be present in the first inorganic slurry and / or the second inorganic slurry. A surfactant can be provided as the wetting agent, but the wetting agent can also include a non-surfactant. In some aspects, the wetting agent can be an organic solvent. If any wetting agent is present, the powder material is uniformly dispersed in an aqueous dispersion of a polyvinylene-based binder. Available wetting agents include ionic and non-ionic surfactants, such as TRITON series (Dow) and PLURONIC series (BASF), BYK-346 (Byk Additives), as well as NMP, DMSO and acetone, but are not limited thereto. The wetting agent includes an organic liquid compatible with the aqueous dispersion, but the present disclosure is not limited thereto. As described above, by dispersing the polymer binder together with the wetting agent in water as a suitable dispersion medium to produce a polymer emulsion, thereby having the first inorganic slurry and / or the second inorganic slurry, pollutants generated during the production process can be minimized.
[0089] According to one embodiment of the present disclosure, the separator 100 is inserted between the negative electrode 300 and the positive electrode 500, and the lamination process of bonding the separator by applying heat and / or pressure is manufactured as an electrochemical device. In one embodiment of the present disclosure, the lamination process can be performed by a roller processing device including a pair of pressure rollers. That is, by stacking the negative electrode, the separator and the positive electrode in sequence and inputting them between the pressure rollers, interlayer bonding can be achieved. In this case, the lamination process can be performed by a hot pressing method.
[0090] One embodiment of the present disclosure provides an electrochemical device including a positive electrode 300 ; a negative electrode 500 ; and a separator 100 interposed between the positive electrode and the negative electrode.
[0091] An electrochemical device according to one embodiment of the present disclosure includes a separator, which does not have a porous polymer substrate, and includes the first inorganic particles that form a dense stacking structure in a sheet shape and can prevent the transition metal dissolved from the positive electrode from transferring to the surface facing the negative electrode, and the second inorganic particles that have a high specific surface area and can adsorb gas and transition metals, thereby improving heat resistance and durability, and improving battery stability and battery life characteristics.
[0092] In this specification, the electrochemical device is a device that converts chemical energy into electrical energy through an electrochemical reaction, and is a concept that includes primary batteries and secondary batteries. In this specification, the secondary battery can be charged and discharged, and refers to a lithium secondary battery, a nickel-cadmium battery, a nickel-hydrogen battery, etc. The lithium secondary battery uses lithium ions as an ion conductor. Examples of the lithium secondary battery may be: a non-aqueous electrolyte secondary battery containing a liquid electrolyte, an all-solid-state battery containing a solid electrolyte, a lithium polymer battery containing a gel polymer electrolyte, a lithium metal battery using lithium metal as a negative electrode, etc., but the present disclosure is not limited thereto.
[0093] According to one embodiment of the present disclosure, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer comprising a positive electrode active material, a conductive material and a binder resin on at least one surface of the current collector. The positive electrode active material may include a layered compound such as a lithium manganese composite oxide (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), or lithium nickel oxide (LiNiO2) or a compound substituted by one or more transition metals; lithium manganese oxide, such as a chemical formula Li 1+x Mn 2-x O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, LiV3O4, V2O5, Cu2V2O7, etc.; 1-x M x Ni-site lithium nickel oxide represented by O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); represented by the chemical formula LiMn 1-x M x A lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (wherein M = Fe, Co, Ni, Cu or Zn); LiMn2O4 in which a part of the chemical formula Li is replaced by an alkaline earth metal ion; a disulfide compound and Fe2(MoO4)3, or a mixture of two or more thereof.
[0094] According to one embodiment of the present disclosure, the negative electrode includes a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, a conductive material, and a binder resin on at least one surface of the current collector. As the negative electrode active material, the negative electrode may include a lithium metal oxide; carbon, such as non-graphitizable carbon or graphitic carbon; a metal composite oxide, such as LixFe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, Group 2, and Group 3 elements of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8); lithium metal; a lithium alloy; a silicon-based alloy; a tin-based alloy; metal oxides, such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; a conductive polymer, such as polyacetylene; a Li-Co-Ni-based material; and a titanium oxide, or a mixture of two or more of them.
[0095] According to one embodiment of the present disclosure, the conductive material may be any one selected from the group consisting of, for example, graphite, carbon black, carbon fiber, metal fiber, metal powder, conductive whiskers, conductive metal oxides, activated carbon, and polyphenylene derivatives, or a mixture of two or more of these conductive materials. More specifically, the conductive material may be any one type selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking carbon black, Denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide, or a mixture of two or more of these conductive materials.
[0096] According to one embodiment of the present disclosure, there is no particular limitation on the current collector as long as it has high conductivity and does not cause a chemical change in the corresponding battery. For example, stainless steel, copper, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used as the current collector.
[0097] According to one embodiment of the present disclosure, a polymer commonly used in industry for electrodes can be used as the binder resin. Non-limiting examples of such binder resins may include vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trichloroethylene copolymer, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan and carboxymethyl cellulose, but the present disclosure is not limited thereto.
[0098] In the present disclosure, the positive electrode slurry used to manufacture the positive electrode active material layer may contain a dispersant. The dispersant may be a pyrrolidone-based compound. Specifically, the dispersant may be N-methylpyrrolidone (ADC-01, LG Chemical Company).
[0099] According to one embodiment of the present disclosure, the content of the dispersant contained in the positive electrode slurry may be greater than 0 parts by weight and less than 0.5 parts by weight relative to 100 parts by weight of the positive electrode slurry. Specifically, the content of the dispersant contained in the positive electrode slurry may be greater than 0.05 parts by weight and less than 0.4 parts by weight relative to 100 parts by weight of the positive electrode slurry.
[0100] According to one embodiment of the present disclosure, the negative electrode slurry used to manufacture the negative electrode active material layer may include a dispersant. The dispersant may be a polypyrrolidone-based compound. Specifically, the dispersant may be polyvinyl pyrrolidone (Japan Junsei Chemical Co., Ltd.).
[0101] According to one embodiment of the present disclosure, the content of the dispersant contained in the negative electrode slurry may be greater than 0 parts by weight and less than 0.5 parts by weight relative to 100 parts by weight of the negative electrode slurry. Specifically, the content of the dispersant contained in the negative electrode slurry may be greater than 0.05 parts by weight and less than 0.4 parts by weight relative to 100 parts by weight of the negative electrode slurry.
[0102] According to one embodiment of the present disclosure, a battery may be manufactured by inserting the electrochemical device prepared as described above into a suitable case and injecting an electrolyte.
[0103] According to one embodiment of the present disclosure, the electrolyte comprises a + B - The electrolyte is obtained by using a salt of the structure A + Including by, for example, Li + 、Na + or K+ ions consisting of alkali metal cations or combinations thereof, and B - Including by, for example, PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - or C(CF2SO2)3 - The organic solvent is composed of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC) or γ-butyrolactone (gamma-butyrolactone) or a mixture thereof, but the present disclosure is not limited thereto.
[0104] One embodiment of the present disclosure provides a battery module, the battery module including a battery including the electrochemical device as a unit cell; a battery pack including the battery module; and a device including the battery pack as a power source. Specific examples of the device may include an electric tool driven by the power of a battery motor; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc.; an electric two-wheeled vehicle including an electric bicycle (E-bike) and an electric scooter (E-scooter); an electric golf cart; a power storage system, etc., but the present disclosure is not limited thereto.
[0105] Invention Mode
[0106] Embodiments will be described in detail below to describe the present disclosure in detail. However, embodiments according to the present disclosure may be modified in various other forms, and the scope of the present disclosure should not be interpreted as being limited to the embodiments described below. The embodiments of this specification are provided to those of ordinary skill in the art to more fully describe the present disclosure.
[0107] <Example 1>
[0108] Synthetic hexagonal boron nitride (hBN) with an aspect ratio of 50 as the first inorganic particle having a flake shape and polyacrylic acid (PAA) as a dispersant were added to NMP (N-methyl-2-pyrrolidone) as a solvent and dispersed for about 30 minutes using an ultrasonic generator to prepare a fluidized slurry.
[0109] A first polymer binder solution containing an acrylic aqueous dispersion (CSB130, Toyo Ink Co., Ltd.) as a polymer binder and a surfactant (FC-4430, Kemis Corporation) was added to the fluid system slurry and dispersed using an ultrasonic generator for about 30 minutes to prepare a first inorganic slurry.
[0110] Then, the first inorganic slurry was applied to one surface of the PET release film and dried. The weight ratio of the first inorganic particles to the polymer binder was 9:1.
[0111] Zeolite Y (silicon to aluminum ratio (SAR) of 1.5 or more) as the second inorganic particles was added to water, dispersed, and basket-milled at 1400 rpm and 1800 rpm for 10 minutes and 50 minutes, respectively, to prepare an aqueous slurry having a reduced particle size (D50: 1 μm or less).
[0112] A second polymer binder solution containing an acrylic water-dispersed emulsion (CSB140, Toyo Ink Co., Ltd.) as a polymer binder and a surfactant (BYK 348) was added to the aqueous slurry 1 hour before coating and subjected to ultrasonic treatment for 30 minutes to prepare a second inorganic slurry.
[0113] Then, the second inorganic slurry was applied to the surface of the first layer including the first inorganic particles and dried. The weight ratio of the second inorganic particles to the polymer binder was 92:8.
[0114] The dispersion was applied to the surface of the second layer including the second inorganic particles by bar coating using a doctor blade, and dried with wind at 50° C. using a heat gun.
[0115] Subsequently, by removing the PET release film, a separator having a total thickness of 13 μm was manufactured.
[0116] <Example 2>
[0117] A separator was manufactured in the same manner as in Example 1, except that the aspect ratio of the first inorganic particles having a flake shape in Example 1 was 200.
[0118] <Comparative Example 1>
[0119] A separator having a thickness of 14 μm was manufactured by the same method as in Example 1, except that in Example 1, one layer was manufactured by adding zeolite Y as the second inorganic particles without the first layer including the first inorganic particles having a flaky shape.
[0120] <Comparative Example 2>
[0121] A separator having a thickness of 11 μm was manufactured using the same method as in Example 1, except that in Example 1, one layer was manufactured by adding hexagonal boron nitride (hBN) as the first inorganic particles having a flaky shape, without the second layer including the second inorganic particles.
[0122] <Comparative Example 3>
[0123] A separator having a thickness of 14 μm was manufactured by the same method as in Example 1, except that the aspect ratio of the first inorganic particles having a flake shape in Example 1 was less than 10.
[0124] <Comparative Example 4>
[0125] A separator having a thickness of 12 μm was manufactured by the same method as in Example 1, except that the aspect ratio of the first inorganic particles having a flake shape in Example 1 was greater than 300.
[0126] <Manufacturing of Electrochemical Device>
[0127] 1) Manufacturing of positive electrode
[0128] The positive electrode active material (LiNi 0.8 Mn 0.1 Co 0.1 O2), conductive material (carbon black), dispersant (N-methylpyrrolidone, ADC-01, LG Chemical Company) and binder resin (mixture of PVDF-HFP and PVDF) were mixed with water in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for a positive electrode active material layer having a concentration of 50% by weight of the remaining ingredients except water. Next, the slurry was applied to the surface of an aluminum film (thickness of 10 μm) and dried to prepare a positive electrode having a positive electrode active material layer (thickness of 120 μm).
[0129] 2) Manufacturing of negative electrode
[0130] Graphite (a mixture of natural graphite and artificial graphite), a conductive material (carbon black), a dispersant (polyvinyl pyrrolidone, Junsei Chemical Co., Ltd.) and a binder resin (a mixture of PVDF-HFP and PVDF) were mixed in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for a negative electrode active material layer having a concentration of 50% by weight of the remaining components except water. Next, the slurry was applied to the surface of a copper thin film (thickness of 10 μm) and dried to prepare a negative electrode having a negative electrode active material layer (thickness of 120 μm).
[0131] 3) Lamination process
[0132] The electrode assembly was obtained by inserting and stacking the separator of each example and comparative example between the prepared negative electrode and the prepared positive electrode and performing a lamination process, which was performed using a hot press at 70° C. and 5.2 MPa for 10 seconds.
[0133] <Experimental Example 1: Air Permeability of Separator>
[0134] The air permeability (Gurley) of the diaphragms of the examples and comparative examples was measured by the ASTM D-2873 method. The Gurley value was measured using a Gurley type air permeability meter (No. 158) manufactured by Toyo Keiki Co., Ltd. in accordance with the JIS Gurley measurement method. The air permeability value is expressed as the time (seconds) required for 100 ml of air to pass through a cross section of 1 square inch of the diaphragm at a pressure of 12.2 inches of H2O, i.e., the air permeability time.
[0135] <Experimental Example 2: Resistance of Separator>
[0136] The separators of each embodiment and comparative example were inserted between SUS to make a coin cell. As the electrolyte of the coin cell, ethylene carbonate:ethyl methyl carbonate was mixed at a volume ratio of 1:2, and LiPF6 was added at a concentration of 1M. The resistance of each coin cell was determined by the analysis results of electrochemical impedance spectroscopy using an analytical device (VMP3, Bio logic Scientific Instruments) at 25°C, an amplitude of 10mV, and a scanning range of 0.1Hz to 1MHz.
[0137] <Experimental Example 3: Breakdown Voltage of Diaphragm>
[0138] The diaphragm samples prepared in each embodiment and comparative example were placed between aluminum fixtures (upper fixture diameter of 30 mm and lower fixture of 50×100 mm) and the voltage when short circuit occurred was tested with a Hi-pot tester. In this case, the test conditions were set to direct current, a current of 0.5 mA, and a voltage increase rate of 100 V / s (maximum 3 kV).
[0139] <Experimental Example 4: Performance Retention Rate of Electrochemical Device>
[0140] In order to evaluate the life of the manufactured electrochemical devices including the separators of Examples and Comparative Examples, each electrochemical device was charged to 4.35 V at 0.33 C and each electrochemical device was discharged to 2.0 V at 0.33 C, the process was performed 500 times, and the initial capacity and the residual capacity were measured.
[0141] <Experimental Example 5: Gas Generation Amount of Electrochemical Device>
[0142] In order to measure the amount of gas generated by the electrochemical devices including the separators of the examples and comparative examples, each electrochemical device was charged and discharged once at 25°C and 0.1C / 0.1C, and the amount of gas generated during the formation was measured. In order to measure the amount of gas generated by the deteriorated battery, the battery evaluated for 500 cycles as in Experimental Example 4 was fully discharged to 2.0V at 0.33C, and the gas generation of the battery was measured.
[0143] <Experimental Example 6: Amount of Transition Metal Dissolution from Electrochemical Device>
[0144] In order to measure the amount of transition metal dissolved from the negative electrode of the electrochemical device comprising the separator of the embodiment and the comparative example, after formation at SOC 30%, 500 charge and discharge tests were performed, wherein the discharge was performed under the conditions of a discharge current density of 0.33C and a discharge voltage of 2.0V, and the charge was performed under the conditions of a charge current density of 0.33C, a charge voltage of 4.35V and constant current-constant voltage (CC-CV). After the 500 cycle tests, the amount of transition metal dissolved from the surface facing the negative electrode was determined.
[0145]
[0146] Referring to Table 1, it can be seen that in Examples 1 and 2 according to the embodiments of the present disclosure, the byproducts not adsorbed by the functional inorganic particles of the second layer do not pass through the layer of inorganic material having a sheet shape (i.e., the first layer) and do not reach the surface facing the negative electrode. Increasing, therefore, on the surface facing the negative electrode of the electrochemical device deteriorated by 500 cycles of discharge, the amount of transition metal dissolution is significantly reduced. It is also confirmed that the improvement of the electrochemical device performance retention rate and the reduction of gas generation due to the same effect.
[0147] In contrast, Comparative Example 1 is a self-supporting ceramic diaphragm composed only of second inorganic particles capable of adsorbing byproducts generated when the electrochemical device deteriorates, and the results show that on the surface of the electrochemical device facing the negative electrode deteriorated by 500 cycles of discharge, the amount of transition metal dissolved is reduced compared to the ordinary diaphragm. Comparative Example 2 is a diaphragm composed only of inorganic particles having a flaky shape (i.e., the first inorganic particles), and since denser inorganic aggregation is possible, it is expected that byproducts accumulated on the surface facing the negative electrode will be reduced by the complex path of transition metal ions. However, compared with Comparative Example 1, the level of Comparative Example 2 is lower. As shown in Comparative Example 3, when the value of the aspect ratio of the inorganic particles having a flaky shape is too small (AR<10), the effect that can be expected by using inorganic particles having a flaky shape is not significant, so the amount of transition metal dissolved on the surface facing the negative electrode, the performance retention rate of the electrochemical device, and the amount of gas generated are poor characteristics. As shown in Comparative Example 4, when the aspect ratio of the flaky inorganic particles is too large (AR>300), it can be confirmed that the flaky inorganic particles hinder the durability of the diaphragm, the breakdown voltage is greatly reduced, and the performance retention rate of the electrochemical device is also at a low level.
[0148] The self-supporting ceramic separator for an electrochemical device according to a specific embodiment of the present disclosure is expected to improve the performance of the electrochemical device by adsorbing gas and preventing by-products from accumulating on the surface facing the negative electrode when the electrochemical device deteriorates because the separator contains a functional inorganic substance and an inorganic substance having a flake shape.
[0149] <Description of symbols>
[0150] 100: Self-supporting ceramic diaphragms for electrochemical devices
[0151] 110: First floor
[0152] 130: Second floor
[0153] 300: Negative
[0154] 500: Positive
Claims
1. A self-supporting ceramic diaphragm for an electrochemical device, comprising: first inorganic particles, second inorganic particles and a polymer binder, wherein the first inorganic particles have a flake shape, and The aspect ratio of the first inorganic particles is 10 or more and 300 or less.
2. The self-supporting ceramic diaphragm according to claim 1, wherein: One surface of the first inorganic material particle and one surface of the separator are arranged to face each other.
3. The self-supporting ceramic diaphragm according to claim 1, further comprising: a first layer, wherein the weight of the first inorganic particles contained therein is greater than the weight of the second inorganic particles contained therein; and The second layer is disposed on a surface of the first layer, wherein the weight of the second inorganic particles contained in the second layer is greater than the weight of the first inorganic particles contained in the first layer.
4. The self-supporting ceramic diaphragm according to claim 3, wherein: A surface of the first layer opposite to the one surface is disposed to face the negative electrode.
5. The self-supporting ceramic diaphragm according to claim 1, wherein: The first inorganic particles include one selected from the group consisting of boron nitride, boehmite, kaolin, and combinations thereof.
6. The self-supporting ceramic diaphragm according to claim 1, wherein: The second inorganic particles are zeolite-based inorganic particles, The second inorganic particles include pores having a diameter of 0.5 nm or more and 0.9 nm or less, and The pores of the second inorganic particles are replaced with metal ions. 7 . The self-supporting ceramic diaphragm according to claim 1 , wherein the average particle size D50 of the second inorganic particles is less than 1 μm. 8 . The self-supporting ceramic diaphragm according to claim 3 , wherein the thickness of the second layer is 1 μm or more and 3 μm or less.
9. The self-supporting ceramic diaphragm according to claim 1, wherein: The content of the first inorganic particles is 5 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the separator.
10. The self-supporting ceramic diaphragm of claim 1, wherein the polymer binder is an acrylic binder, a polyvinylene binder, or a combination thereof.
11. The self-supporting ceramic diaphragm according to claim 1, wherein: The separator has a thickness of 7 μm or more and 15 μm or less.
12. The self-supporting ceramic diaphragm according to claim 1, wherein: The air permeability of the separator is 170 sec / 100 cc or less.
13. The self-supporting ceramic diaphragm according to claim 1, wherein: The separator has an electrical resistance of 0.6Ω or more and 1.2Ω or less. 14 . An electrochemical device comprising a positive electrode, a negative electrode, and the separator according to claim 1 , wherein the separator is interposed between the positive electrode and the negative electrode.
Citation Information
Patent Citations
filter unit
KR1020230051554A